The Relationship of Obesity and Central Obesity with the Incidence of Hypertension in the Binanga Health Center District of Mamuju - Hasmar Fajriana; Firdaus Syafii (Hypertension Prevention and Control Research Center, The Polytechnic of Health of Banten, 2023)
Hypertension is a non-communicable disease (NCD) that is still a global health problem, including in Indonesia. The prevalence of hypertension increases with age. There are several factors that contribute to the incidence of hypertension in Indonesia, including obesity and central obesity. This study aims to determine the relationship between obesity and central obesity and the incidence of hypertension in the work area of the Binanga Community Health Center, Mamuju Regency. This research is an observational study using a cross-sectional design. The population in this study were all participants in the integrated coaching post (posbindu) in the working area of the Binanga health center, and a sample of 204 people was taken using total sampling techniques. Data were collected by interview, measuring body weight, height, and blood pressure. The data obtained were analyzed using the chi-square test. The study results showed that the proportion of respondents suffering from hypertension was 47.7%. Based on the study, it was concluded that there was a significant relationship between age (p-value = 0.000) and obesity (p-value = 0.043) and the incidence of hypertension. Meanwhile, gender (p-value = 0.065) and central obesity (p-value = 0.230) were not significantly related to the incidence of hypertension.